Effect of Preconception, Prenatal and Postnatal Exposure to Ambient Air Pollution on Laryngitis in Southern Chinese Children - Liu, Yanlin; Deng, Miaomiao; Zhang, Duo; Lu, Chan; Lu, Shaoyou (Frontiers in Environmental Science, 2022)
Environmental exposure is considered to be a main triggering factor of laryngitis, a common upper respiratory tract infection, especially in developing countries. However, unclear detrimental air pollutants and lack of understanding on their early-life exposure and laryngitis warrant further investigation. Therefore, a retrospective cohort including 2328 preschool children was conducted during 2015‒2016 in Shenzhen, China. We measured ambient air quality of PM10, SO2 and NO2 in 12 monitoring stations, and obtained childhood laryngitis prevalence and confounding covariates by questionnaire. Multiple logistic regression analysis showed that the lifetime prevalence of childhood laryngitis (12.2%) was associated with an interquartile range increase in late preconception [odds ratio (95% confidence interval, CI): 1.43 (1.06‒1.92)], prenatal [1.35 (1.02–1.79)] and early-postnatal [1.32 (1.11‒1.57)] exposure to SO2. Sensitivity analysis revealed that this relationship appeared more obvious among boys without parental atopy, mold/damp stains, or window condensation. Nevertheless, there was no relationship between early-life PM10 and NO2 exposure and childhood laryngitis. These findings suggest that early-life exposure to SO2 significantly increases risk of childhood laryngitis. Preventive measures need to be implemented to mitigate industrial air pollution.